ADAPTASI SKALA PROSOCIALNESS FOR ADULT VERSI BAHASA INDONESIA - Detri Sefianmi; Chandra Yudistira Purnama; Amir N. Setyadiredja (Jurnal Psikologi, 2023)
This study adapts and analyzes the psychometric properties of Prosocialness for Adults developed by Caprara in Indonesian with a sample of university students. The adaptation of this measuring instrument goes through several stages, starting from translation, back translation, testing the reliability coefficient, and collecting validity evidence in the form of content-based testing and internal structure testing using confirmatory factor analysis (CFA). This study involved a sample of students in Bandung and Cimahi, as many as 273 students. The results showed that the Indonesian version of PSA Scale was declared reliable (alpha Cronbach = 0.841) and met the goodness of fit index criteria. Indonesian version of the PSA Scale measuring instrument has good psychometric properties, so it can be used for research or assessment purposes that measure degree prosocial in adolescent samples. This study suggests that the Indonesian version of the PSA Scale can be developed by adding a wider variety of samples, a larger sample size, and trying to relate to other variables to increase criterion validity